2014
DOI: 10.1104/pp.114.246694
|View full text |Cite
|
Sign up to set email alerts
|

Cotton WRKY1 Mediates the Plant Defense-to-Development Transition during Infection of Cotton byVerticillium dahliaeby ActivatingJASMONATE ZIM-DOMAIN1Expression    

Abstract: Plants have evolved an elaborate signaling network to ensure an appropriate level of immune response to meet the differing demands of developmental processes. Previous research has demonstrated that DELLA proteins physically interact with JASMONATE ZIM-DOMAIN1 (JAZ1) and dynamically regulate the interaction of the gibberellin (GA) and jasmonate (JA) signaling pathways. However, whether and how the JAZ1-DELLA regulatory node is regulated at the transcriptional level in plants under normal growth conditions or d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
91
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 138 publications
(101 citation statements)
references
References 88 publications
7
91
0
3
Order By: Relevance
“…As T 0 W1RNAi silencing transgenic plants had poor seed setting, we were unable to get viable T 1 generation. As previously shown in cotton, this might be due to dual role of WRKY1 in plant growth and development as well as in defence (Li et al ., ), and thus, WRKY1 silencing might have affected seed setting resulting into loss of viable T 1 generation. Two independent W1OE lines (W1OE‐1 and W1OE‐8) exhibited significant elevation of SlWRKY1 transcripts (15‐ and 21‐fold, respectively) compared to wild‐type (WT) plants in the absence of pathogen (Figure S10a).…”
Section: Resultsmentioning
confidence: 99%
“…As T 0 W1RNAi silencing transgenic plants had poor seed setting, we were unable to get viable T 1 generation. As previously shown in cotton, this might be due to dual role of WRKY1 in plant growth and development as well as in defence (Li et al ., ), and thus, WRKY1 silencing might have affected seed setting resulting into loss of viable T 1 generation. Two independent W1OE lines (W1OE‐1 and W1OE‐8) exhibited significant elevation of SlWRKY1 transcripts (15‐ and 21‐fold, respectively) compared to wild‐type (WT) plants in the absence of pathogen (Figure S10a).…”
Section: Resultsmentioning
confidence: 99%
“…VW is caused by soil‐borne fungus Verticillium dahliae , which worldwide invades more than 400 plant species hosts (Li et al ., ; Zhang et al ., ). This disease will lead to chlorosis and wilt of leaves or defoliation, the browning of vascular and even death ultimately (Li et al ., ; Xu et al ., ). It has been the major challenge for cotton and deserves enormous researches to control efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…Global analyses have demonstrated that several signaling pathways, including those mediated by salicylic acid, ethylene, jasmonic acid, and brassinosteroids, activate distinct processes involved in V. dahliae defense (Bari and Jones, 2009;Grant and Jones, 2009;Gao et al, 2013a). Accumulating evidence indicates that many V. dahliae-responsive genes, such as GbWARKY1, GhSSN, GbERF, GhMLP28, GhNDR1, GhMKK2, and GhBAK1 (Qin et al, 2004;Gao et al, 2011Gao et al, , 2013bLi et al, 2014a;Sun et al, 2014;Yang et al, 2015), play crucial roles in defense against Verticillium wilt. In addition, the biosynthesis of terpenoids, lignin, and gossypol also makes important contributions to V. dahliae resistance in cotton (Tan et al, 2000;Luo et al, 2001;Xu et al, 2011;Gao et al, 2013a).…”
mentioning
confidence: 99%